Microplastics and mesoplastics in fish from coastal and fresh waters of China. (February 2017) - Jabeen, Khalida; Su, Lei; Li, Jiana; Yang, Dongqi; Tong, Chunfu; Mu, Jingli; Shi, Huahong
Abstract: Plastic pollution is a growing global concern. In the present study, we investigated plastic pollution in 21 species of sea fish and 6 species of freshwater fish from China. All of the species were found to ingest micro- or mesoplastics. The average abundance of microplastics varied from 1.1 to 7.2 items by individual and 0.2–17.2 items by gram. The average abundance of mesoplastics varied from 0.2 to 3.0 items by individual and 0.1–3.9 items by gram. Microplastics were abundant in 26 species, accounting for 55.9–92.3% of the total number of plastics items in each species. Thamnaconus septentrionalis contained the highest abundance of microplastics (7.2 items/individual). The average abundance of plastics in sea benthopelagic fishes was significantly higher than in freshwater benthopelagic fishes by items/individual. The plastics were dominanted by fiber in shape, transparent in color and cellophane in composition. The proportion of plastics in the stomach to the intestines showed great variation in different species, ranging from 0.5 to 1.9 by items/individual. The stomach of Harpodon nehereus and intestines of Pampus cinereus contained the highest number of plastics, (3.3) and (2.7), respectively, by items/individual. Our results suggested that plastic pollution was widespread in the investigated fish species and showed higher abundance in comparison with worldwide studies. The ingestion of plastics in fish was closely related to the habitat and gastrointestinal tract structure. We highly recommend that the entire gastrointestinal tract and digestion process be used in future investigations of plastic pollution in fish. Graphical abstract: Highlights: Plastic pollution was widespread in sea fishes and freshwater fishes from China. The occurrence of microplastics was dominant in fishes. Plastics in the stomach and intestine showed great variation in different species. We recommend the entire GIT should be used in fish. Abstract : High levels of plastics occurred not only in the stomach but also in the intestines of fishes from China.